1004 I Was Sleeping, Or So I Thought: Comparison Of Subjective And Objective Reports In Individuals With Alcohol Dependence During An Inpatient Rehabilitation Treatment Program. (27th April 2018) - Tuason, R; Brooks, A; Krumlauf, M; Li, Y; Raju, S; Ding, Y; Wallen, G
Abstract: Introduction: Current evidence suggests that there is discordance between subjective and objective assessments of sleep quality in various patient populations. Little is known about the concordance between subjective and objective measures of sleep among individuals with alcohol dependence, who experience higher rates of sleep disturbance compared to the general population. Methods: Data were collected from a cohort of patients (n=164) enrolled on an inpatient alcohol treatment program. Both objective (actigraphy) and subjective (Pittsburgh Sleep Quality Index-PSQI and daily diaries) measures of sleep quantity and quality were collected. PSQI assessments from day 28 of inpatient treatment and the first four weeks average actigraphy sleep duration and efficiency were compared using a paired t-test. Sleep efficiency was calculated by dividing total sleep duration by the total time spent in bed during major rest intervals. Results: Of the 96 patients included in this analysis, the majority were male (66.7%), non-Hispanic (95.8%), and African American (51%). Self-reported sleep duration (6.17 hrs ± 1.47) was significantly (p < 0.0001) longer than actigraphy recorded sleep duration (5.17 hrs ± 1.17). In addition, there were significant differences (p < 0.0001) between self-reported (87.05% ± 15.21%) and actigraphy-recorded (74.87% ± 11.12%) sleep efficiency. Conclusion: In a population of individuals undergoing inpatient treatment for alcohol dependence, our data demonstrate a significant discordance between the patients' subjective reports of sleep efficiency and actigraphy-recorded sleep efficiency. Discordance between subjective and objective reports of sleep efficiency and duration may have clinical implications especially when it comes to the treatment of sleep disturbance among individuals with alcohol use disorders. Understanding individual-level predictors of concordance between subjective and objective sleep measures should be further explored. Support (If Any): This project has been funded with federal funds from the NIH Clinical Center and the NIAAA intramural research programs. The content of this publication does not necessarily reflect the views or policies of the Department of Health and Human Services, nor does it imply endorsement by the U.S. Government.